Beverages Consumption and Oral Health in the Aging Population: A Systematic Review - Zupo, Roberta; Castellana, Fabio; De Nucci, Sara; Dibello, Vittorio; Lozupone, Madia; Giannelli, Gianluigi; De Pergola, Giovanni; Panza, Francesco; Sardone, Rodolfo; Boeing, Heiner (Frontiers in Nutrition, 2021)
Little study has yet been made of the effect of different beverages on oral health outcomes in the aging population. The purpose of this systematic review is to evaluate the association between different beverages, including alcohol intake, coffee, milk, tea, and sugary drinks, and a cluster of oral health outcomes, including periodontal disease, oral dysbiosis, and tooth loss in older adults. The literature was screened from the inception up to May 2021 using six different electronic databases. Two independent researchers assessed the eligibility of 1308 retrieved articles regarding inclusion criteria; only 12 fitted the eligibility requirements, representing 16 beverage entries. A minimum age of 60 was the inclusion criterion. No exclusion criteria were applied to outcomes assessment tools, recruiting facilities (hospital or community), general health status, country, and study type (longitudinal or cross-sectional). The consumption of alcoholic beverages was expressed as alcohol intake in all eligible studies, thereby replacing alcoholic beverages in the analysis. The quality of evidence was judged as moderate for alcohol and low or very low for beverages. In regard to oral health in the elderly, the review identified information on alcohol (56.25%), followed by coffee (18.75%), milk (12.50%), tea (6.25%), and sugary drinks (6.25%). Alcohol, sugary drinks, and coffee were found to be related to tooth loss. Periodontal disease was inversely related to coffee and milk, but fostered by alcohol consumption. In one article, tea but not coffee seemed to improve oral microbiota. In summary, alcohol seems to be a driver for tooth loss and periodontal disease in the aging population. However, more research is needed to gain a more solid knowledge in this research area. Systematic Review Registration:https://www.crd.york.ac.uk/prospero/, PROSPERO, Identifier: CRD42021256386.